PEMBELAJARAN KOOPERATIF TEKNIK MAKE A MATCH DALAM PENINGKATAN HASIL BELAJAR IPS SISWA KELAS IV SD - setyowati, amrih (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract:. Cooperative Learning Techniques Make a Match in Improved IPS Learning Outcomes Fourth Grade Students of Elementary School. The purposes of this research was improve IPS learning outcomes fourth grade students of elementary school with cooperative learning teknik Make a Match. This research is a collaborative action research conducted in three cycles, each cycle includes the planning, implementation, observation and reflection. This research subjects were students and teachers. This research data comes from teachers, students, and observers. Data collection technique in this research using test, observation, questionnaires, and documentation. The data validity in this research using triangulation techniques and triangulation of data collection techniques. This research results show that of cooperative learning techniques Make a Match can improve IPS learning outcomes fourth grade students of elementary school.Keywords: Make a Match, IPS learning outcomesAbstrak : Pembelajaran Kooperatif Teknik Make a Match dalam Peningkatan Hasil Belajar IPS Siswa Kelas IV SD. Penelitian ini bertujuan untuk meningkatkan hasil belajar IPS siswa kelas IV SD dengan pembelajaran kooperatif teknik Make a Match. Penelitian ini adalah penelitian tindakan kelas kolaboratif yang dilaksanakan dalam tiga siklus, masing-masing siklus mencakup tahap perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian ini adalah siswa dan guru. Data penelitian ini berasal dari guru, siswa, dan observer. Teknik pengumpulan data dalam penelitian ini menggunakan tes, observasi, angket, dan dokumentasi. Validitas data dalam penelitian ini menggunakan teknik triangulasi sumber dan triangulasi teknik pengumpulan data. Hasil penelitian ini menunjukkan bahwa pembelajaran kooperatif teknik Make a Match dapat meningkatkan hasil belajar IPS siswa kelas IV SD.   Kata Kunci: Make a Match, hasil belajar IPS